2016
DOI: 10.1186/s12864-016-3183-3
|View full text |Cite
|
Sign up to set email alerts
|

Recombination events among virulence genes in malaria parasites are associated with G-quadruplex-forming DNA motifs

Abstract: BackgroundMalaria parasites of the genus Plasmodium possess large hyper-variable families of antigen-encoding genes. These are often variantly-expressed and are major virulence factors for immune evasion and the maintenance of chronic infections. Recombination and diversification of these gene families occurs readily, and may be promoted by G-quadruplex (G4) DNA motifs within and close to the variant genes. G4s have been shown to cause replication fork stalling, DNA breakage and recombination in model systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
91
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(105 citation statements)
references
References 53 publications
(93 reference statements)
13
91
1
Order By: Relevance
“…In bacteria, G-quadruplexes are found in Escherichia coli [161], Neisseria gonorrhoeae [162], Neisseria meningitidis [163], Mycobacterium tuberculosis [164], and Deinococcus radiodurans [165]. G-quadruplexes were also found in ciliates [14], malaria parasites [166,167], and yeasts [168,169]. Notably, helicases that resolve G-quadruplex structures, such as RecQ [170,171] and Pif1 [142] families, were found in both nonhuman and human systems.…”
Section: G-quadruplexes In Nonhuman Genomesmentioning
confidence: 99%
“…In bacteria, G-quadruplexes are found in Escherichia coli [161], Neisseria gonorrhoeae [162], Neisseria meningitidis [163], Mycobacterium tuberculosis [164], and Deinococcus radiodurans [165]. G-quadruplexes were also found in ciliates [14], malaria parasites [166,167], and yeasts [168,169]. Notably, helicases that resolve G-quadruplex structures, such as RecQ [170,171] and Pif1 [142] families, were found in both nonhuman and human systems.…”
Section: G-quadruplexes In Nonhuman Genomesmentioning
confidence: 99%
“…In addition to HIV-1 evolution, other functional aspects of G4s discussed in this review, and the selective retention or exclusion of G4s from specific genomic loci in bacteria and yeast, indicate that G4s play a role in the evolution of microbes ( Figure 3) [30,[37][38][39][40][41][42].…”
Section: Recombination-[ 3 1 9 _ T D $ D I F F ] Mediated Microbial Ementioning
confidence: 92%
“…Interestingly, about a quarter of all putative quadruplex motifs in the P. falciparum genome are associated with the promoters of the var genes [29]. Stanton et al identified a close association between the recombination breakpoints and G4 motifs in P. falciparum [30]. Breakpoints were found to occur proximal to quadruplexes, especially in subtelomeic regions, indicating that G4s have a role in var-associated recombination.…”
Section: Antigenic Variationmentioning
confidence: 99%
“…falciparum. The motifs strongly associate with recombination breakpoints that were observed in var genes when parasites were cultured over many mitotic cycles, evolving new gene variants [21]. Furthermore, the knockdown of a RecQ helicase homolog called PfWRN dramatically increased the rate of var gene recombination, as would be expected if this helicase was responsible for unwinding G4s and modulating their recombinogenic effects [22].…”
mentioning
confidence: 98%
“…reichenowi, and potentially also in P. knowlesi, which has sicavar genes rather than var genes [21].…”
mentioning
confidence: 99%